Is the use of videotape recording superior to verbal feedback alone in the teaching of clinical skills? - Yildirim Ediz; Gunvar Tolga; Guldal Dilek; Mevsim Vildan; Ozcakar Nilgun; Sisli Zafer; Semin Ilgi (BMC, 2009)
Abstract Background In recent times, medical schools have committed to developing good communication and history taking skills in students. However, there remains an unresolved question as to which constitutes the best educational method. Our study aims to investigate whether the use of videotape recording is superior to verbal feedback alone in the teaching of clinical skills and the role of student self-assessment on history taking and communication skills. Methods A randomized controlled trial was designed. The study was conducted with 52 of the Dokuz Eylul University Faculty of Medicine second year students. All students' performances of communication and history taking skills were assessed twice. Between these assessments, the study group had received both verbal and visual feedback by watching their video recordings on patient interview; the control group received only verbal feedback from the teacher. Results Although the self-assessment of the students did not change significantly, assessors' ratings increased significantly for videotaped interviews at the second time. Conclusions Feedback based on videotaped interviews is superior to the feedback given solely based on the observation of assessors.